Maximizing the power of entertainment. The audience commodity in contemporary radio. - Stiernstedt, Fredrik (Radio Journal: International Studies in Broadcast & Audio Media, 2008)
This article explores the reconfigurations of the control and monitoring of the audience that take place in concert with the digitalization that characterize contemporary radio broadcasting. Three technologies for the automation of audience research and consumer monitoring are analyzed: MediaScore, used for online media research (in this case music tests); the iSelector for customizing music streams online, and the Personal People Meter (PPM) for the production of ratings. Drawing on analysis from an ethnographic fieldwork at eight music radio stations the article concludes that the work of producing the audience commodity within the radio industry is changing. Research is increasingly becoming a way to bond with listeners, turning audience self-disclosure into a part of media consumption as such. At the same time, as shown in the article, the three technologies distributes the responsibility of the research process to the people researched upon, meanwhile facilitating a more generalized surveillance. The expanded surveillance through digital media seems also to have other objectives than the previous production of audience statistics. This could be characterized as a shift from using quantitative to using qualitative data, in producing the audience commodity.